Alimentary necrobacillosis in alpacas. (March 2020) - Carvallo, Francisco R.; Uzal, Francisco A.; Flores, Carlos; Diab, Santiago S.; Giannitti, Federico; Crossley, Beate; Wünschmann, Arno
Ulcers of the oral cavity, esophagus, and gastric compartments of South American camelids are uncommon. Multifocal-to-coalescing ulcers were identified in the oral cavity, esophagus, and/or gastric compartments of 5 alpacas submitted for postmortem examination. Fusobacterium necrophorum was isolated from the lesions in all alpacas, in combination with other aerobic and anaerobic bacteria. In 4 of these cases, F. necrophorum –associated lesions were considered secondary to neoplasia or other chronic debilitating conditions; in 1 case, the alimentary ulcers were considered the most significant autopsy finding. It is not known if this agent acted as a primary or opportunistic agent in mucosal membranes previously damaged by a traumatic event, chemical insult, immunodeficiency, or any other debilitating condition of the host.